Real-Time Virtual Teaching: Lessons Learned From a Case Study in a Rural School - Barbour, Michael K. (Online Learning, 2015)
Due to the challenges facing rural schools, many jurisdictions have resorted to the use of virtual school programs to provide curricular opportunities to their students. While the number of virtual schools that rely on synchronous instruction as a primary or significant method of delivery is quite small, there are some programs that do (and a growing number of virtual schools that use it with small groups or individuals). This case study examined the use of synchronous online instruction by one virtual school with students in a single rural school in Newfoundland and Labrador. The data from a variety of collection methods revealed three themes: similarities with online student experiences and their traditional classroom experiences, the development of local learning communities, and the preference for students to use chat over audio.